TANTANGAN BELAJAR MANDIRI KURIKULUM MERDEKA SDN KUIN CERUCUK 1 - Akhmad Rafi'i; Diani Ayu Pratiwi; Romamarisa Putri Utami; Nazwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of the Merdeka Curriculum in elementary schools has brought positive impacts on learning approaches, one of which is the emphasis on independent learning. This study aims to identify the challenges faced by students in optimizing independent learning in the era of the Merdeka Curriculum. The research method used is descriptive, with data collected through interviews and documentation. The findings indicate that students face difficulties in learning independently. Factors such as social background, cognitive abilities, and the presence of students with special needs (SEN) influence the effectiveness of independent learning. SDN Kuin Cerucuk 1 has 22 students with special needs who are supported by five specialized teachers. This assistance is a positive step in ensuring they continue to receive equal access to education. Regular students also face challenges, such as being reluctant to communicate their learning difficulties. Factors that can enhance the effectiveness of independent learning include the school’s efforts in providing guidance and the involvement of parents in the learning process. The lack of material review at home and minimal parental support also contribute to students’ slow understanding of lessons taught in class.